PEMANFAATAN INSTAGRAM SEBAGAI MEDIA KOMUNIKASI PEMASARAN ONLINE PADA NIACAKE (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
Marketing communication is an important part of marketing a product. So that each company uses several media to do marketing one of the media, namely Instagram. This study aims to describe Niacake's use of Instagram as a marketing communication medium. This research uses a marketing communication approach with a qualitative descriptive research type. Data were analyzed inductively from the results of interviews, observations, and documentation. The research informants have the status of Niacake owners, Niacake employees, and Niacake consumers. The results show that Niacake uses Instagram as an online marketing communication medium in marketing its products using the marketing mix theory (4P), namely product, price, place, and promotion. Niacake's use of Instagram as a marketing communication medium has been utilized as a whole with several features on Instagram, one of which is promoting the endorsement of Niacake products on the instastory. The marketing communication model used by Niacake is a macro communication process model, Niacake as the sender of messages delivers messages to consumers via Instagram in the form of product introductions, prices, sales locations, and discounts which are then translated by consumers by liking, commenting, and purchasing Niacake products.